The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41539-018-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

No intrinsic gender differences in children’s earliest numerical abilities

Abstract: Recent public discussions have suggested that the under-representation of women in science and mathematics careers can be traced back to intrinsic differences in aptitude. However, true gender differences are difficult to assess because sociocultural influences enter at an early point in childhood. If these claims of intrinsic differences are true, then gender differences in quantitative and mathematical abilities should emerge early in human development. We examined cross-sectional gender differences in mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 82 publications
(101 reference statements)
8
56
1
4
Order By: Relevance
“…Overall, our results indicate that female and male students experience different levels of STEM anxiety and exhibit different neurobiological systems-level support for this anxiety, which differentially impacts their academic success. That this occurs despite no sex differences in performance (e.g., GPA or course grade) is notable, and in agreement with two recent meta-analyses that provide strong evidence disproving the persistent stereotypes that male students outperform female students in math and science (Kersey et al, 2018;O'Shea et al, 2018). Importantly, the course studied here was shown to be equal (i.e., did not adversely impact female anxiety more than male anxiety), but not equitable (i.e., did not reduce sex differences).…”
Section: Discussionsupporting
confidence: 85%
“…Overall, our results indicate that female and male students experience different levels of STEM anxiety and exhibit different neurobiological systems-level support for this anxiety, which differentially impacts their academic success. That this occurs despite no sex differences in performance (e.g., GPA or course grade) is notable, and in agreement with two recent meta-analyses that provide strong evidence disproving the persistent stereotypes that male students outperform female students in math and science (Kersey et al, 2018;O'Shea et al, 2018). Importantly, the course studied here was shown to be equal (i.e., did not adversely impact female anxiety more than male anxiety), but not equitable (i.e., did not reduce sex differences).…”
Section: Discussionsupporting
confidence: 85%
“…With this perspective, some studies even suggest that the STEM gender gap starts from inborn differences between sexes regarding STEM aptitudes. However, this stereotype has been thoroughly revised in Reference [9], where the authors have analyzed possible gender differences in mathematical cognition from 500 children aged from six months to eight years. This analysis found that boys and girls do not show any difference in terms of quantitative or mathematical ability, thus they have the same aptitudes in terms of mathematical reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are studies that indicate no gender differences are observed in children's early mathematical skills (Kersey, Braham, Csumitta, Libertus, and Cantlon 2018), including first years of primary school (Hutchison, Lyons, and Ansari 2018), traditionally, the differences have been reported on. At the same time, the findings focusing on the differences remain inconsistent, seeking caution in interpretation.…”
Section: Gender Differences In Arithmeticmentioning
confidence: 98%